miR-146a inhibits mitochondrial dysfunction and myocardial infarction by targeting cyclophilin D - Qiang Su; Yuli Xu; Ruping Cai; Rixin Dai; Xiheng Yang; Yang Liu; Binghui Kong (Elsevier, 2021)
Increasing evidence suggests that mitochondrial microRNAs (miRNAs) are implicated in the pathogenesis of cardiovascular diseases; however, their roles in ischemic heart disease remain unclear. Herein, we demonstrate that miR-146a is enriched in the mitochondrial fraction of cardiomyocytes, and its level significantly decreases after ischemic reperfusion (I/R) challenge. Cardiomyocyte-specific knockout of miR-146a aggravated myocardial infarction, apoptosis, and cardiac dysfunction induced by the I/R injury. Overexpression of miR-146a suppressed anoxia/reoxygenation-induced cardiomyocyte apoptosis by inhibiting the mitochondria-dependent apoptotic pathway and increasing the Bcl-2/Bax ratio. miR-146a overexpression also blocked mitochondrial permeability transition pore opening and attenuated the loss of mitochondrial membrane potential and cytochrome c leakage; meanwhile, miR-146a knockdown elicited the opposite effects. Additionally, miR-146a overexpression decreased cyclophilin D protein, not mRNA, expression. The luciferase reporter assay revealed that miR-146a binds to the coding sequence of the cyclophilin D gene. Restoration of cyclophilin D reversed the inhibitory action of miR-146a on cardiomyocyte apoptosis. Furthermore, cardiomyocyte-specific cyclophilin D deletion completely abolished the exacerbation of myocardial infarction and apoptosis observed in miR-146a cardiomyocyte-deficient mice. Collectively, these findings demonstrate that nuclear miR-146a translocates into the mitochondria and regulates mitochondrial function and cardiomyocyte apoptosis. Our study unveils a novel role for miR-146a in ischemic heart disease.